PROBLEMATIKA PENDAFTARAN TANAH ADAT MENJADI HAK MILIK TANPA PERSETUJUAN SELURUH AHLI WARIS PADA KANTOR PERTANAHAN KABUPATEN SAMOIR - AGUSMAN RODEKA SIREGAR (PREMISE LAW JURNAL, 2017)
ABSTRACT Adat law on adat land in the Batak Toba community, Samosir Regency, becomes the main attention in scientific measure. Batak Toba ethnic group that reside in Samosir is generally farmers. Therefore, it is undeniable that they have different perspective on land, compared with the other ethnic groups in Indonesia, including legal concept on the State with adat land. Rapid economic development also needs land in economic activity such as buy and sell, let and sublet, and burden of land rights on collateral for the credit so that the longer the time is, the more the need for legal certainty in land rights. The title of the research was “The Problems in the Registration of Adat Land to Become Proprietary Rights without the Approval of all Heirs at the Land Office of Samosir Regency”. Keywords: Problems, Adat Land, Propriety Rights